Promoting human-centred AI in the workplace. Trade unions and their strategies for regulating the use of AI in Germany - Martin Krzywdzinski; Detlef Gerst; Florian Butollo (Transfer: European Review of Labour and Research, 2022)
The use of artificial intelligence (AI) is changing the world of work. For trade unions, the issue of how to regulate the use of AI is a central but difficult topic because the technology is still at an early stage and experience on its use limited. Focusing on Germany, this article addresses the following questions: (1) what areas of application and use cases for AI are relevant for trade unions and works councils?, (2) what role do trade union positions and demands play in the political discussion on regulating the use of AI?, (3) what strategies are trade unions using to influence the regulation and use of AI in the workplace?, and (4) what experiences are they gaining during this process? Reviewing trade union strategies, this article shows which concepts of human-centred AI the trade unions are trying to promote, how they try to ensure that works councils and trade unionists get appropriate training to understand the new technologies, and how dealing with AI is changing the way works councils work. The article also shows how the characteristics of the German system of industrial relations influence discussions on AI and the processes of implementing it in the workplace. – – Der Einsatz künstlicher Intelligenz (KI) verändert die Arbeitswelt. Für die Gewerkschaften ist die Frage, wie der Einsatz von KI am Arbeitsplatz reguliert werden soll, ein zentrales, aber schwieriges Thema, denn diese Technologie befindet sich noch in einem frühen Entwicklungsstadium, und die Erfahrungen mit ihrer Verwendung sind begrenzt. Der vorliegende Artikel befasst sich in erster Linie mit Deutschland und geht folgenden Fragen nach: (1) Welche Anwendungsbereiche und Anwendungsfälle für KI sind relevant für Gewerkschaften und Betriebsräte? (2) Welche Rolle spielen Standpunkte und Forderungen der Gewerkschaften in der politischen Diskussion über die Regulierung des Einsatzes von KI? (3) Welche Strategien nutzen die Gewerkschaften, um Einfluss auf die Regulierung und den Einsatz von KI am Arbeitsplatz zu nehmen? und (4) Welche Erkenntnisse gewinnen sie im Rahmen dieses Prozesses? Der vorliegende Artikel stellt Gewerkschaftsstrategien für eine menschenzentrierte KI vor. Diese umfassen Qualifizierungsstrategien für Betriebsräte und Gewerkschafter:innen und Veränderungen in deren Arbeitsweise. Der Artikel zeigt zudem, wie die Eigenheiten des deutschen Systems der Arbeitsbeziehungen die Diskussionen über KI und die Prozesse der Implementierung dieser Systeme beeinflussen.
Keywords: 330; industrial relations; trade unions; co-determination; technological change; digitalisation; artificial intelligence